ORAL CHANGES IN PATIENTS WITH CHRONIC RENAL FAILURE - Belazelkovska A.; Popovska M.; Spasovski G.; Belazelkovska Z.; Minovska A.; Mitic K. (Romanian Journal of Oral Rehabilitation, 2013)
Aim: To make comparative evaluation of objective oral clinical findings and subjective oral symptoms in patients with chronic renal failure (CRF) undergoing various therapeutic treatments, and to find possible link between subjective symptoms and objective clinical findings. Material and methods: We examined 90 patients with chronic renal failure divided into three groups: patients with CRF undergoing hemodialysis, patients with CRF without hemodialysis and serum creatinine <120μmol / L and patients with renal transplantation. Swab for Candida Albicans was taken from the oral mucosa. Oral changes were followed on the entire mucosal surface of the oral cavity and were classified into subjective and objective findings. Results: Certain oral changes showed a predisposition to a particular group of patients, such as petechiae and ecchymoses in the dialysis group and gingival enlargement in transplant group. Coated tongue, thirst, pale oral mucosa and dry fissured lips were the most frequent oral symptoms and changes among all CRF patients independently in which group they have belonged. Significant association was found between xerostomia and coated tongue and between unpleasant taste and coated tongue in all studied patients. Conclusion: The stadium and consequently severity of chronic renal disease as well as the type of treatment have influence on the severity of the oral clinical finding.